Poisons sociaux Histoire des stupéfiants en Grèce (1875-1950) - Gkotsinas, Konstantinos (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2022)
Social poisons analyse why and how, at the end of the 19th and the beginning of the 20th centuries, the consumption of toxic substances became a social issue that stirred up great concern among contemporaries. By using a wide variety of sources (legislative texts, police archives, diplomatic documents, criminological, medical and psychiatric publications, press articles, literary works and other artistic creations, such as the popular rebetika songs), the book sheds a new light on the advent of "drug addiction". This complex historical process had numerous features: it included the medical and recreational use of psychoactive substances, restrictive policies on the production, trade and consumption of narcotics, as well as broader and historically defined fears of Greek society, in a period that was in many respects transitional. Indeed, it was during this time that Greek territory and population more than doubled, when the question of modernisation was raised emphatically, and developments, such as the mass arrival of new populations, the redefinition of women's role, and the emergence of new ideological currents, swayed traditional points of reference and the established order.The book addresses these aspects, and documents the form and extent of drug use in Greece by setting it in its legislative, social and cultural framework on the one hand, and in the broader context of the history of narcotics in Eastern Mediterranean, Europe and the world on the other. In doing so, Social Poisons offer both an original and unconventional viewpoint on the history of Greece at the early 20th century, and a historical background for contemporary discussions and public debate on drug policies.